ANALISIS KEPUASAN PENGGUNA LULUSAN INSTITUT TEKNOLOGI KALIMANTAN DENGAN METODE RATING SCALE - Haliq, Ridhwan; Sulistyowati, Ria Adha; Millah, Nasrul (Jurnal Vokasi Indonesia, 2020)
In the world of work, the quality of employees is very concerned about supporting smooth work. Companies definitely choose prospective employees who have the qualities that the company expects. because of this, universities are required to develop soft skills that are balanced with hard skills. In addition to the quality of graduates, universities must also know the needs of companies and adjust to DUDI (world of work and industry). This will have an impact on graduates who will enter the world of work. The better the name of the college, the greater the opportunity for college graduates to join the company. In this study will be analyzed the satisfaction and needs of users passed by the Kalimantan Institute of Technology based on user satisfaction surveys with the target company or where alumni work. This research uses the Rating Scale method which is a systematic and structured observation method in reporting evaluation results, where each indicator used will be weighted according to the satisfaction survey data obtained.